BULIMIA: TRATAMENTO NUTRICIONAL E PSICOLÓGICO - Sebotaio, Ana Luisa Concli; Giehl, Franciele; Trennepohl, Letícia; Junges, Luana Roberta; Fernandes, Rui Gabriel; Schorn, Solange Castro (Salão do Conhecimento, 2019)
Trabalho de pesquisa realizado no curso Nutrição da Unijuí.